Standardized nuclear markers improve and homogenize species delimitation in Metazoa. Issue 2 (11th December 2022) - Dietz, Lars; Eberle, Jonas; Mayer, Christoph; Kukowka, Sandra; Bohacz, Claudia; Baur, Hannes; Espeland, Marianne; Huber, Bernhard A.; Hutter, Carl; Mengual, Ximo; Peters, Ralph S.; Vences, Miguel; et al.
Abstract: Species are the fundamental units of life and evolution. Their recognition is essential for science and society. Molecular methods have been increasingly used for the identification of animal species, despite several challenges. Here, we explore with genomic data from nine animal lineages a set of nuclear markers, namely metazoan‐level universal single‐copy orthologs (metazoan USCOs), for their use in species delimitation. Our data sets include arthropods and vertebrates. We use various data assembly strategies and use coalescent‐based species inference as well as population admixture analyses and phenetic methods. We demonstrate that metazoan USCOs distinguish well closely related morphospecies and consistently outperform classical mitochondrial DNA barcoding in discriminating closely related species in different animal taxa, as judged by comparison with morphospecies delimitations. USCOs overcome the general shortcomings of mitochondrial DNA barcodes, and due to standardization across Metazoa, also those of other approaches. They accurately assign samples not only to lower but also to higher taxonomic levels. Metazoan USCOs provide a powerful and unifying framework for DNA‐based species delimitation and taxonomy in animals and their employment could result in a more efficient use of research data and resources.